Pengembangan Media Video Animasi pada Mata Pelajaran IPAS Kelas IV Sekolah Dasar (Indo-MathEdu Intellectuals Journal, 2024)
Students have difficulty understanding one of the materials in the science and science subject, namely the material on changes in the form of substances. The problem with this material is that students have difficulty understanding changes in substance form and examples of substance form changes. This research aims to produce animation video media for science science subjects in grade IV elementary school that is valid, practical, and effective. The type of research used is research and development (R&D), using the 4-D development model. The validity test was carried out by 3 validators, namely 1 material validator and 2 media validators. The practicality test was carried out on 27 fourth grade students of SD Negeri 05 Air Tawar Barat with the aim of finding out the practicality and effectiveness of the product. The validation results from the material expert validators obtained an average of 4.83 with the category of "very valid". The results of the assessment of 2 media validators obtained an average of 4.81 with the category of "very valid". The results of the media practicality test obtained an average score of 4.48 with the category of "very valid". The results of the effectiveness test using classical completeness showed that of the 27 students who completed it, there were 23 students with a percentage of 85% exceeding the classical completeness requirement, namely ≥ 75% of students who completed their learning outcomes. Based on the results of the validity, practicality, and effectiveness tests, it can be concluded that the resulting animation video media is feasible and effective so that it can be used in elementary school grade IV science subjects